TRIZ-based S-curve analysis of evolutionary trend of LED lights. (2017) - Zhang, Xin; Peng, Liang
With the evolution of technology systems, main parameters of value (MPV) show an S-curve development with time. This paper presents a general TRIZ-based S-curve analysis of the technology evolution of LED lights as well as the similarities and differences in the evolution of incandescent lamps, gas discharge lamps and LEDs. S-curve analysis is strategically meaningful in making technical development plans, and evolution laws will facilitate in predicting the future of LEDs. Understanding them will offer possibilities for tool-assisted problem solving.